Kemudahan Penggunaan dan Manfaat Melakukan Transaksi Penarikan Tunai Tanpa Kartu Menggunakan Mobile Banking - Riza, Akmal; Iskandar, Evy; Rahayu, Nining Puji (EKOBIS SYARIAH, 2026)
This study aims to examine cardless cash withdrawal transactions through mobile  banking and their role in increasing transaction intention in Islamic banking. Specifically, the research investigates the effects of perceived ease of use and perceived benefit on users’ intentions to conduct cardless cash withdrawal transactions using BSI Mobile among students at UIN Ar-Raniry in Banda Aceh. A quantitative research approach with an associative design was employed. Primary data were collected through a structured questionnaire distributed to 100 student BSI Mobile users, selected using a non-probability sampling technique with purposive sampling. The data were analyzed using multiple linear regression method to test the proposed hypotheses. The results reveal that perceived usefulness has a positive and significant effect on users’ intention to conduct cardless cash withdrawal transactions via BSI Mobile. In contrast, perceived ease of use has no effect on transaction intention. These results provide valuable insights into the determinants of digital banking service adoption among university students, particularly in the context of Islamic banking.